English Educational Game Development Using Unity with a Gamification Approach for Elementary School Students - Irfan Afriantoro; Desvi Ramadhani Syafitri; Candra Naya (Universitas Mohammad Husni Thamrin, 2026)
English is an international language that has an important role in the era of globalization, especially in the field of education. However, learning English at the elementary school level still has challenges that must be faced, namely conventional teaching methods that make children bored. Because in these methods only teachers or mentors are more active than students as well as the lack of motivation in students. This research aims to overcome these challenges by developing an android-based educational game using unity as its game engine. The game also use a gamification approach by taking the element of points or scores. The game development method used in this research is Multimedia Development Life Cycle (MDLC). The game will focus on the introduction of vocabulary objects, colors, animals, and fruits that can be played by one person per device. This research is expected to produce an English educational game with an android-based gamification approach that can improve the learning motivation of elementary school children, increase student involvement in learning, and is expected to be an effective learning tool for teachers or mentors to help elementary school children learn English.